"Old Princeton" and Westminster: The Relationship of Biblical and Systematic Theology - Lillback, Peter (Verbum Christi: Journal of Reformed Evangelical Theology, 2023)
Historic continuity exists between the "Old Princeton" and Westminster Theological Seminary in Philadelphia. While this continuity could be considered from various vantage points, it is especially evident in how theologians from both institutions have engaged in the interrelationship between biblical and systematic theology. These theological traditions have had an abiding concern for interpreting the Scriptures correctly due to their deep commitment to the authority of the biblical canon.